Expression and penetrance of the hereditary pancreatitis phenotype in monozygotic twins. Issue 4 (1st April 2001) - Amann, S T; Gates, L K; Aston, C E; Pandya, A; Whitcomb, D C
Abstract : BACKGROUND: Hereditary pancreatitis (HP) is a rare autosomal dominant disorder with variable expression and an overall lifetime penetrance of 80%. We hypothesised that (1) monozygotic twins within similar environments would develop the typical signs of HP at a similar age, and (2) if penetrance were due to modifier genes or environment, all twin pairs would be concordant for expression of HP. AIM: Identify monozygotic twins with HP and determine the penetrance, concordance, and age of onset of symptoms. METHODS: Twins from HP kindreds were identified from the Midwest Multicenter Pancreatic Study group database, referrals, and literature searches. Each twin set was assessed for phenotypic expression, concordance, and difference in age of phenotypic onset of pancreatitis. The difference in onset of symptoms for symptomatic affected non-twin sibling pairs as well as non-twin pairs that were mutation, sex, and age matched were calculated as two comparison groups. RESULTS: Seven of 11 monozygotic pairs identified were suitable for evaluation and four were concordant for pancreatitis. Forty eight affected sibling pairs and 33 pairs of mutation, sex, and age matched (cationic trypsinogen R122H (30 pairs) and N29I (three pairs)) subjects were identified for comparison groups. The median (quartiles Q1, Q3) difference in the age of phenotypic onset in the concordant twins was 1 (0, 2.4) years, 2 (1, 6) for the affected siblings, and 7 (2, 15) years in the comparison control group. Three of the seven sets of twins (43%) were discordant for phenotypic expression of pancreatitis. The overall penetrance in the seven pairs of monozygotic twins was 78.6%. CONCLUSIONS: Genetic and/or environmental factors contribute to expression and age of onset of HP. Nuclear genes or general environmental factors alone cannot explain the 80% penetrance. Determining the mechanism of non-penetrance may help in developing a strategy to prevent the phenotypic expression of pancreatitis in individuals with an underlying genetic predisposition.